2014
DOI: 10.5539/gjhs.v7n3p52
|View full text |Cite
|
Sign up to set email alerts
|

The Topical Effect of Grape Seed Extract 2% Cream on Surgery Wound Healing

Abstract: Background:Reducing the wound healing time is crucial in wound as it lowers the chance of infection and decreases complications and cost. Grape seed extract has the ability to release endothelial growth factor and its topical application results in contraction and closure of the skin wound. Furthermore, it possesses antioxidant and antibacterial properties. In several studies it has been proved effective in animals. Therefore, due to low side effects and recognition of herbal medicine, we decided to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 13 publications
1
37
0
2
Order By: Relevance
“…Their findings showed that in the intervention and placebo groups, complete wound healing occurred, respectively, on the eighth and the fourteenth post-surgery days, respectively. Their statistical analyses showed a significant difference between the groups regarding the time of achieving recovery (P < 0.001) (19). In line with our findings, their findings confirmed the positive effects of grape seed extract on wound healing.…”
Section: Discussionsupporting
confidence: 89%
“…Their findings showed that in the intervention and placebo groups, complete wound healing occurred, respectively, on the eighth and the fourteenth post-surgery days, respectively. Their statistical analyses showed a significant difference between the groups regarding the time of achieving recovery (P < 0.001) (19). In line with our findings, their findings confirmed the positive effects of grape seed extract on wound healing.…”
Section: Discussionsupporting
confidence: 89%
“…PCs also helps in promoting the formation of collagen and elastin and preservation of skin moisture. Furthermore, PCs induces vascular endothelial growth factor, reduces edema and encourages blood flow thereby accelerates wound healing [28][29][30][31][32][33]. Khanna et al reported the outcome of grape seed extract (GSE) on in-vivo wound healing among nine male BalbC mice.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that the use of herbal medicines may accelerate the wound healing process by promoting growth factor release. For example, grape seed extract triggers the release of VEGF [ 16 ]. R. damascena is also involved in the enhancement of neurite outgrowth [ 17 ].…”
Section: Discussionmentioning
confidence: 99%